Loss of social role awareness, a subdomain of social frailty, is an independent predictor of future adverse events in hospitalized older patients with heart failure. (3rd October 2022) - Katano, S; Watanabe, A; Nagaoka, R; Numazawa, R; Honma, S; Ohori, K; Kouzu, H; Fujito, T; Nishikawa, R; Ohwada, R; Nagano, N; Koyama, M; et al.
Abstract: Background: Frailty is a complex syndrome characterized by a decline in functional reserve, and associated with aging and chronic diseases including heart failure (HF). The impact of physical frailty on prognosis and the effect of cardiac rehabilitation in HF patients have been well established. However, the data on the prognostic impact of social frailty (SF) in HF patients is limited. Aims: We aimed to get new insight into mechanisms of the association of SF with clinical outcomes in older hospitalized HF patients. Methods: A single-center, retrospective cohort study was conducted using data from 308 HF patients aged ≥65 years (mean age of 78±8 years; 49% females) who were admitted to our institute for the management of HF. SF was assessed using the validated Makizako's five questions. The following responses were considered positive for SF: (1) going out less frequently compared with last year; (2) not visiting friends; (3) not talking with someone every day; (4) not feeling helpful toward friends or family; and (5) living alone. SF was defined as two or more positive responses. The primary outcome was composite events defined by all-cause death and cardiovascular events. The missing data were imputed using multiple imputation by chained -equations algorithm. Results: Of 308 older HF patients, 189 patients (61%) were SF. Patients with SF were significantly older, had lower body mass index, and a higher percentage of patients with physical frailty and cognitive frailty than those without SF. Seventy-five patients (24%) experienced composite events during a median follow-up period of 1.55-years (interquartile range, 0.88–2.20 years). Kaplan-Meier curves showed a significantly higher composite event rate in patients with SF than those without SF. In multivariate Cox regression analyses, SF was independently associated with a higher composite event rate after adjusting for pre-existing risk factors [adjusted hazard ratio (HR), 1.91; 95% confidence interval (CI), 1.09–3.35; p=0.03] (Figure 1A). In addition, further analyses showed that only the positive response on the question corresponding to the social role – not feeling helpful toward friends or family – among the questionnaire was an independent predictor for the incidence of the composite event (adjusted HR, 2.10; 95% CI, 1.29–3.41; p<0.01, Figure 1B). Inclusion of the response to the question regarding the social role into the baseline prognostic model improved the accuracy of prediction of the composite event (continuous net reclassification improvement, 0.46; 95% CI, 0.21–0.71; p<0.01; integrated discrimination improvement, 0.025; 95% CI 0.004–0.047; p=0.02; Figure 2). Conclusion: Loss of social role awareness was associated with increased composite event risk and provided additive prognostic information in older HF patients, suggesting the importance of healthcare professionals' decision-making on the prevention and management of SF. Funding Acknowledgement: Type of funding sources: None.